Sinergi Guru Dan Orang Tua Dalam Pengawasan Penggunaan Gadget Anak Usia Dini Berdasarkan Nilai Keislaman - Hairunnisa, Hairunnisa (AUD Cendekia: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze the integration of digital technology in Islamic education learning for early childhood at PAUD Terpadu Harokah and to assess its impact on the effectiveness of teaching Islamic values. Using a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and documentation involving teachers, principals, and parents. The findings reveal that the implementation of digital technology—such as interactive videos, Islamic learning applications for children, and educational animations—has enhanced students’ learning interest, understanding of Islamic concepts, and active participation in classroom activities. The integration of technology also strengthens the introduction of Islamic values, including manners, moral character, worship practices, and tauhid, in a contextual and engaging way. However, the study also indicates that the use of digital technology must be balanced with direct habituation of Islamic values to maintain children’s social and spiritual interactions. This research emphasizes the importance of collaboration between teachers and parents in guiding the use of technology aligned with the principles of Islamic education. The findings contribute theoretically to the development of a model for integrating digital technology in Islamic education and provide practical recommendations for Islamic early childhood institutions to optimize digital-based learning that fosters both character and spiritual values.